Comorbid epilepsy and depression—pharmacokinetic and pharmacodynamic drug interactions - Miziak, Barbara; Czuczwar, Stanisław J.; Pluta, Ryszard (Frontiers in Pharmacology, 2022)
Background: Major depressive disorder may be encountered in 17% of patients with epilepsy and in patients with drug-resistant epilepsy its prevalence may reach 30%. This indicates that patients with epilepsy may require antidepressant treatment. Purpose: Both pharmacodynamic and pharmacokinetic interactions between antiepileptic (antiseizure) and antidepressant drugs have been reviewed. Also, data on the adverse effects of co-administration of antiepileptic with antidepressant drugs have been added. Methods: The review of relevant literature was confined to English-language publications in PUBMED databases. Table data show effects of antidepressants on the seizure susceptibility in experimental animals, results of pharmacodynamic interactions between antiepileptic and antidepressant drugs mainly derived from electroconvulsions in mice, as well as results concerning pharmacokinetic interactions between these drugs in clinical conditions. Conclusion: Antidepressant drugs may exert differentiated effects upon the convulsive threshold which may differ in their acute and chronic administration. Animal data indicate that chronic administration of antidepressants could reduce (mianserin, trazodone) or potentiate the anticonvulsant activity of some antiepileptics (fluoxetine, reboxetine, venlafaxine). There are also examples of neutral interactions (milnacipran).